A systematic review of the socio-economic impacts of large-scale tree plantations, worldwide - Malkamäki, A.; D'Amato, D.; Hogarth, N.J.; Kanninen, M.; Pirard, R.; Toppinen, A.; Zhou, W. (Elsevier, 2018)
Since their widespread introduction in the 1980s, large-scale tree plantations have seen contestations over their socio-economic impacts. With the establishment of new plantations on the rise, a review of the literature examining their impacts on local communities is needed to inform policies and practices. In this systematic review, we followed an a priori protocol to reduce the selection biases inherent to conventional literature reviews, and considered both grey and peer-reviewed literature. Of the 20,450 studies identified in our literature search, only 92 studies met our predefined inclusion criteria. However, only 22 studies presented a clear comparator and considered confounding factors in their analysis. Of the 251 impacts identified in this sample, most impacts across the nine categories were characterised as predominantly negative impacts attributed to large-scale tree plantations. Impacts on employment (22% of reported impacts/of which 41% predominantly negative), land (21%/81%), livelihoods (12%/48%) and the often intertwined social impacts (20%/69%) were the most commonly considered categories, within which a majority of studies agreed on the impact dynamics when in similar contexts, resembling the dynamics observed in other large-scale land-based investments. Most impacts were reported from Southeast Asia (34% of reported impacts), South America (29%), Africa (23%) and Australasia (12%). We corroborate that costs of large-scale tree plantations for residents tend to be front-loaded, especially when plantations have displaced customary land uses, and possible benefits to accrue over time, moderated by the emergence of local processing and complementary livelihood activities. However, given the methodological inconsistencies in our sample and the under-representation of areas known to have undergone plantation development, strong global evidence on the long-term socio-economic impacts of large-scale tree plantations remains limited.